Peran Sanggar Seni Kesumba Dalam Melestarikan Kesenian Tradisional Melayu - Oktariani, Dwi (Journal Ilmiah Rinjani : Media Informasi Ilmiah Universitas Gunung Rinjani, 2024)
The Malay tribe in West Kalimantan is a native or indigenous population originating from the land of Indonesian Kalimantan. The current real situation is that some traditional works of art are extinct and some are on the verge of extinction. The lack of a platform or media to get to know and study art is one of the reasons why traditional art is difficult to maintain. This article examines the role of the Kesumba Art Studio in preserving traditional Malay arts in the Mempawah area and its surroundings. This research aims to gain knowledge about the role of kesumba studios in seeking the existence of traditional arts in West Kalimantan. The data in this research is written in qualitative descriptive form which will present it in the form of words. A sociological approach is taken to better understand the results of observations, interviews, documentation, data analysis and results. The results of this research are that the Kesumba Art Studio is a studio that is still trying to maintain traditional Mempawah arts by developing, re-teaching and displaying them so that the arts do not become extinct. The role of the Kesumba Art Studio in traditional arts is as a forum or shelter for a number of art practitioners, as a medium for education in the form of non-formal education, as entertainment for the community of art enthusiasts, as a place to organize strategies regarding the arts they pursue, as an arts community, as a source of income for activists art and strengthen brotherhood. must be factual and concise. Keywords: Kesumba Art Studio,role, preserving art ABSTRAK Suku Melayu di Kalimantan Barat adalah penduduk asli atau pribumi yang berasal dari tanah Kalimantan Indonesia. Kondisi real sekarang ini sebagian karya seni tradisional punah dan sebagian lagi diujung kepunahan. Kurangnya wadah atau media untuk mengenal dan mempelajari sebuah kesenian merupakan salah satu alasan mengapa kesenian tradisional sulit untuk dipertahankan. Tulisan ini mengupas peran Sanggar Seni Kesumba dalam menjaga kelestarian kesenian tradisional melayu di daerah Mempawah dan sekitarnya. Penelitian ini bertujuan untuk mendapatkan pengetahuan tentang peran sanggar kesumba dalam mengupayakan eksistensi kesenian tradisional di Kalimantan Barat.  Data-data dalam penelitian ini ditulis dalam bentuk deskriptif kualitatif yang akan mengangkatnya dalam bentuk kata-kata. Pendekatan sosiologi dilakukan untuk lebih mengetahui hasil dari observasi,wawancara, dokumentasi, analisis data higga hasil. Hasil dari penelitian ini yaitu Sanggar Seni Kesumba merupakan sanggar yang masih berupaya mempertahankan kesenian tradisional Mempawah dengan cara mengembangkan, mengajarkan kembali, hingga menampilkannya agar kesenian tersebut tidak punah. Peranan Sanggar Seni Kesumba dalam kesenian tradisional adalah sebagai wadah atau tempat bernaung sejumlah pelaku seni, sebagai media edukasi dalam bentuk Pendidikan nonformal, sebagai hiburan masyarakat sekitar peminat seni, sebagai tempat mengatur strategi seputar seni yang ditekuni, sebagai paguyuban seni, sebagai sumber penghasilan bagi pegiat seni serta mempererat persaudaraan. harus faktual dan ringkas. Kata kunci: Sanggar Kesumba, Peran, Melestarikan Kesenian